Reversible and fast responsive optical fiber relative humidity sensor based on polyelectrolyte self-assembly multilayer film - Gu, Bobo (2019)
A high-performance fiber-optic relative humidity (RH) sensor was prepared by layer-by-layer self-assembly of polycation, poly (4-vinylpyridinium chloride), and polyanion, sodium alginate, on the surface of a thin-core fiber modal interferometer. The process of layer-by-layer self-assembly was monitored by UV-vis spectroscopy and surface profilometer. The morphology of the fabricated multilayer film was characterized by atomic force microscopy and field emission scanning electron microscopy. A fast, reversible, and linear response to RH with a high resolution of 0.1 nm/1% RH has been experimentally demonstrated by the proposed fiber-optic sensor.